Manufaktur Dan Pemasangan Komponen Avionik Pada UAV Skywalker 1900 Dengan Material Komposit Berpenguat Fiber Carbon - Setiawan, Ferry; Febriyanto, Chandra; Wira Samudra, Elang; Wichaksono, Dhimas; Zulfikar Ramdhan, Muhammad; Satria Maulana, Dede (Manutech : Jurnal Teknologi Manufaktur, 2023)
This research is a collaboration between STTKD Yogyakata and Frogs Indonesia, a startup that manufactures flying vehicles, with the aim of making the UAV Skywalker 1900 flying vehicle with Carbon Fiber reinforced composite materials to produce a structure that is stronger than the material commonly used, namely Styrofoam. The initial stage of making the UAV was to work on the Skywalker 1900 UAV design drawings and printed them with 3D printing using PLA Filament, the 3D printing results were then molded using Epoxy resin. From the resulting molding, the structure of the aircraft parts will be made with fiber glass reinforced composite materials using the Vacuum Bagging method. After the structure of the aircraft parts is completed, the electrical and avionic components are installed. The flight test results of the Skywalker 1900 UAV aircraft have a speed of around 15 m/s to 20 m/s, the weakness of this aircraft design is that it is still difficult to control, from the existing analysis this is caused by the aerofoil on the horizontal stabilizer causing lift in the tail of the aircraft of 1 newtons.